Delineation of downstream signalling components during acrosome reaction mediated by heat solubilized human zona pellucida - Talwar Pankaj; Bansal Pankaj; Bhandari Beena; Gupta Satish K (BMC, 2010)
Abstract Background Human egg is enveloped by a glycoproteinaceous matrix, zona pellucida (ZP), responsible for binding of the human spermatozoa to the egg and induction of acrosomal exocytosis in the spermatozoon bound to ZP. In the present manuscript, attempts have been made to delineate the downstream signalling components employed by human ZP to induce acrosome reaction. Methods Heat-solubilized human ZP (SIZP) was used to study the induction of acrosome reaction in capacitated human spermatozoa using tetramethylrhodamine isothiocyanate conjugated Pisum sativum agglutinin (TRITC-PSA) in absence or presence of various pharmacological inhibitors. In addition, intracellular calcium ([Ca2+]i) levels in sperm using Fluo-3 acetoxymethyl ester as fluorescent probe were also estimated in response to SIZP. Results SIZP induces acrosomal exocytosis in capacitated human sperm in a dose dependent manner accompanied by an increase in [Ca2+]i. Human SIZP mediated induction of acrosome reaction depends on extracellular Ca2+ and involves activation of Gi protein-coupled receptor, tyrosine kinase, protein kinases A & C and phosphoinositide 3 (PI3)- kinase. In addition, T-type voltage operated calcium channels and GABA-A receptor associated chloride (Cl-) channels play an important role in SIZP mediated induction of acrosome reaction. Conclusions Results described in the present study provide a comprehensive account of the various downstream signalling components associated with human ZP mediated acrosome reaction.